Modeling and simulation of walking robots with 3 dof legs - Silva, Manuel (2019)
This paper describes a simulation model for a multilegged locomotion system with 3 dof legs and leg joint actuators having saturation. For that objective the robot prescribed motion is characterized in terms of several locomotion variables. Moreover, the robot body is divided into several segments in order to emulate the behavior of an animal spine. A non-linear spring-dashpot system models the foot-ground interaction, being its parameters computed from studies on soil mechanics. To conclude, the performance of the developed model is evaluated through a set of experiments while the robot leg joints are controlled using a proportional and derivative algorithm.